KARAKTERISTIK KIMIA, FISIKA DAN ORGANOLEPTIK CUKO PEMPEK BUBUK DARI BERBAGAI FORMULASI GULA SEMUT DAN SUKROSA CHEMICAL, PHYSICAL, AND ORGANOLEPTIC OF CUKO PEMPEK POWDER FROM SUGAR ANTS AND SUCROSE FORMULATION - Syukri, Alhanannasir Syukri; Suyatno, Suyatno; Handi, M. Tri Handi (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2014)
Sugar is an indispensable component in the manufacturing process cuko pempek, including in the manufacture of pempek cuko powder. This study aims to test the sugar ants and sucrose formulations against chemical properties, physical and organoleptic cuko pempek powder. This study used a randomized block design are arranged in a non fakorial formulation with treatment factors and sucrose sugar ants on making cuko pempek powder consisting of five factors and the treatment was repeated four times. Parameters observed in this study is the chemical analysis includes analysis of total sugar content and physical tests include viscosity and velocity soluble. As for organoleptic tests include flavor, color and scents cuko pempek powder by using multiple comparison test. Treatment formulation of sugar ants and sucrose on making cuko pempek powder very significant effect on the total sugar content and viscosity of soluble cuko pempek speed powder. Sugar content was highest in the treatment of C5 with an average value of 64.828%, the highest level of consistency found in the C1 treatment with an average value of 3.492 cPs and time is needed to dissolve the speed at which the C5 treatment 8.30 seconds. Multi-sensory test data flavor and scents, color cuko pempek powder obtained that treatment has treatment C1 sense of color, and aroma, no real different to the cuko pempek standard. Plural formulation test C1 has a flavor (37.50%), color (38.39%) and scents (46.43%), which is almost the same as the cuko pempek standard.